EVALUASI KINERJA ESP DN1800 UNTUK MENAIKAN PRODUKTIVITAS SUMUR MINYAK - Fajar Anggara (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2021)
The use of the Electrical Submersible Pump (ESP) in the oil lifting method is very popular because it is easy to install, less required installation of tools in the field and a high efficiency. To achieve the Q target, ESP parameters such as the number of stages and RPM need to be analyzed to align with the IPR (Inflow Performance Flow) curve. The use of nodal analysis is used to determine the relationship between Pwf and head pump. Iteration needs to be done to determine the range of the number of stages so that it aligns with characteristics of well. It is found that the recommended range stage is 580-600 at a well depth of 7684 ft. Moreover, it is found that with 3600 RPM and 600 stages is able to reach the Q target. The relationship between the number of stages and RPM value with Pwf is inversely proportional.